The Dangers of Marine Pollution on Consumer Health, Economic Value, and Aesthetic Value in Human Life - Wijaya, Haryadi; Dien, Henny Adeleida; Montolalu, Roike Iwan; Makapedua, Daisy Monica (Jurnal Ilmiah Platax, 2024)
Water pollution happening in the sea results in changes to the composition or structure of the water affected by human activities and natural processes. This leads to water having qualities and functions that do not align with their intended uses and can disrupt human life, marine biota, and marine ecosystems. Pollution in the marine ecosystem undoubtedly affects marine products in various aspects of life. This article used a literature review method to gather the necessary data for explaining the discussed topic. This article aims to explain the harmful impacts of marine pollution on consumer health, economic value, and the aesthetic value of the marine ecosystem. Based on the results of literature studies conducted through secondary data analysis from published journals in the last 10 years (2015-2024), it was found that marine pollution contaminated with bacteria or pathogens due to chemical substances can disrupt human health, causing symptoms such as vomiting, diarrhea, stomach pain, collapse, and even death. The economic aspect also experienced its impacts, such as the decrease in fishermen's catch and the disruption of the beauty of the marine ecosystem due to changes in water composition, leading to the sea appearing cloudy and odorous, and being filled with waste. Keywords: Dangers of Marine Pollution, Consumer Health, Economy, Aesthetics